Peer Variables and Academic Identification of Senior Secondary School Students in Uyo Education Zone of Akwa Ibom State - Isong, Hannah Bassey; Ugochukwu, victor; Okoro, Cornelius Christopher; Udofia, Nsika-Abasi (Advances in Social Sciences Research Journal, 2021)
The purpose of this correlational study was to investigate the relationship between peer variables (peer acceptance, peer support and peer loyalty) on young adolescents’ academic identification. The sub variables; PA, PS and PL were examined using a researcher made instrument titled School Peer Variable Questionnaire ( α=0.86). Academic Identification was measured using the standardized Osborne (1997) Identification with Academic Scale which has (r 0.92). Sample selected was (N = 544). Responses were scored and hypotheses tested at .05 level of significance using the PPMC. Findings revealed the importance of peer relationship on both academic and emotional adjustment of adolescent learners. Peer acceptance, support and loyalty were found to improve learners’ chances of achieving positive academic outcomes. The implication for educators and other stakeholders in adolescent care giving and teaching is for them to understand the importance of maintaining healthy peer relationships for young learners as teacher and peer acceptance, peer support and peer loyalty help them meet psychogenic needs and promote their academic motivation, self-concept, participation, classroom engagement, and feelings of belongingness in the school .Thus, findings have immense significance for educational research and practice, and also bodes well for teachers and counselors in Nigerian secondary schools. urban, ethnically